1989
DOI: 10.1002/pros.2990140206
|View full text |Cite
|
Sign up to set email alerts
|

Binding of epidermal growth factor by human normal, hypertrophic, and carcinomatous prostate

Abstract: Saturable binding sites for radioiodinated epidermal growth factor (EGF) have been quantified in surgical specimens of benign prostate hypertrophy (BPH), histologically normal (HN) prostate, and prostate cancer. Values for EGF binding did not differ significantly between HN prostate and prostate cancer, although dedifferentiated samples tended to higher levels. These were coincident with lower comparative levels of androgen receptors. Unfractionated BPH tissue contained lower levels of EGF binding than either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
3

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 34 publications
3
38
0
3
Order By: Relevance
“…Higher levels of EGFR expression in DU145 and PC3 compared with LNCaP have been reported at the transcriptional level (Morris and Dodd, 1990;Ching et al, 1993) and by ligand binding (Davies and Eaton, 1989). Our results extended those findings by showing increased EGFR expression at the translational level in PC3 and DU145 cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Higher levels of EGFR expression in DU145 and PC3 compared with LNCaP have been reported at the transcriptional level (Morris and Dodd, 1990;Ching et al, 1993) and by ligand binding (Davies and Eaton, 1989). Our results extended those findings by showing increased EGFR expression at the translational level in PC3 and DU145 cells.…”
Section: Discussionsupporting
confidence: 87%
“…In addtiion, our studies demonstrated that androgen-independent but not androgen-sensitive, prostatic tumour cell lines express higher levels of EGFR than normal prostatic epithelial cells. None of the in vivo studies have adequately addressed the issue of relative EGFR expression in androgen-sensitive and androgen-independent prostate cancer, although Davies and Eaton (1989) have reported an inverse relationship between EGF binding and androgen receptor expression in homogenized specimens of prostatic carcinoma. Results of the present study showed that elevated expression and activation of EGFR were associated with the androgenindependent phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the EGF/TGFα receptor, previously reported in the literature (Davies & Eaton 1989), was first confirmed in the clone of cells used in our laboratory. The identity of the 170 kDa band, expected to be the EGF/ TGFα receptor, was then validated by autoradiography of the immunoprecipitated labeled phosphoproteins using a specific monoclonal antibody raised against the EGF/ TGFα receptor.…”
Section: Effects Of Somatostatin On the Phosphorylation Of The Egf/tgsupporting
confidence: 73%
“…The latter cell line is highly invasive and metastatic, and has greatly increased EGFRs (Zhau et al, 1996). Most of these cell lines are growth-stimulated by EGF and TGF-α in culture (Davies and Eaton, 1989;Ching et al, 1993), and growth-inhibited by EGFR antibodies (Ennis et al, 1989;Mendelsohn, 1992). Moreover, recent data indicate that chimeric monoclonal EGFR antibodies can significantly inhibit the growth of DU145 and PC3 cell xenografts in nude mice (Prewett et al, 1997).…”
mentioning
confidence: 99%